The Role of Public Administration in Natural Disaster Mitigation and Its Implications for Economic Stability - Rijal, Syamsu; Suherlan; Ausat, Abu Muna Almaududi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Indonesia, situated within the Pacific Ring of Fire and tropical regions, faces significant vulnerability to natural disasters such as earthquakes, tsunamis, volcanic eruptions, and floods. Its geographical conditions heighten the risk of frequent natural disasters, which often have extensive and profound impacts on society and the economy. This study aims to analyze the role of public administration in natural disaster mitigation and its implications for economic stability. It employs a literature review methodology with a qualitative approach, drawing data from scholarly articles available on Google Scholar from 2011 to 2024. The findings underscore the critical importance of public administration in disaster mitigation for maintaining the economic stability of the country. Indonesia, as a nation vulnerable to various natural disasters, has experienced serious human and material losses. The response from the government and related agencies, such as the National Disaster Management Agency (BNPB), has been pivotal in coordinating mitigation efforts, emergency response, and post-disaster recovery